Construing the child reader: a cognitive stylistic analysis of the opening to Neil Gaiman’s The Graveyard Book - Giovanelli, Marcello (Springer, 2016)
Neil Gaiman’s The Graveyard Book (2009) charts the story of Nobody Owens, a boy who is adopted by supernatural entities in the local graveyard after his family is murdered. This article draws on the notion of the “construed reader,” and combines two cognitive stylistic frameworks to analyse the opening section of the novel. In doing so, the article explores the representation and significance of the family home in relation to what follows in the narrative. The analysis largely draws on Text World Theory (Werth, 1999; Gavins, 2007), but also integrates some aspects of Cognitive Grammar (Langacker, 2008), which allows for a more nuanced discussion of textual features. The article pays particular attention to the way Gaiman frames his narrative and positions his reader to view the fictional events from a distinctive vantage point and subsequently demonstrates that a stylistic analysis of children’s literature can lay bare how such writing is designed with a young readership in mind.